The environmental impacts and social challenges of coastal tourism in Pasikudah - Rewathy, K.; Nuskiya, M.H.F. (SEUIARS 2018, South Eastern University of Sri Lanka, 2019)
Coastal tourism development and management is a massive complex phenomenon which throws threatening towards marine life, habitat conservation, and social stability. Sri Lanka is a wealthy country based on the resources that have itself. Natural beauty is the major influence of its economy. Though the nation is facing social related issues along with the less per capita, it manages to improve its fundamental facilities, basic needs and wellbeing of people. This paper is mainly considering tourism as being one of the major economic sectors in Sri Lanka. Sri Lanka has the capability to satisfy the need of travelers with its natural beauty. Though there are numerous destinations for tourism, this study focused on the Pasikudah tourist place in Batticaloa. Even though the tourism of the study area giving lots of benefits to the individuals, there are diverse impacts on the environment and social well-being. Therefore, by using primary and secondary data this study involved in identifying the core issues and challenges of tourism in Pasikudah and the surrounded settlement areas. Primary data played a major role to identify the negative and positive impacts whilst secondary data used to identify the parallel situation of tourism and integration of tourist places. Eventually the study concluded with the overall analysis of data. Positive impacts influenced by the native folks for their economy and negative impacts were identified in the environmental degradation and land use. Migration, mangrove, and coral reef destruction occurring gradually in the Pasikudah region. There is a drastic increase in the arrival of tourists in the Pasikudah area from 2009 after the civil war. Hence the sustainable tourism in Pasikudah is still a chance to be executed. Changing the tourism industry through the eco-tourism in the tourism industry in the Pasikudah region will be the best solution. Keywords: tourism, environment, impact, development, sustainability